Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26480/mjsa.01.2021.43.50
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Combination With Biochar: Improving Yield and Quality of Jute Seed

Abstract: Plants are naturally growing on the soil without hampering the eco-friendly environment. Intensive cultivation of crops with high yielding verities (HYV) hampering the soil health resulting unfertile soil. In addition, frequent uses of chemicals as well as overdose of synthetic fertilizer creating hazardous environment for the living things. However, to meet up the demand of foods as well as other basic requirements of increasing population of the world crop cultivation techniques need to be modernized. To ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Lower Cr VI availability and plant accessibility showed excellent sorption ability of JBCs and JPBCs [22]. In a review study about ameliorating effects of BC on physio-chemical properties of weather soil, Glaser et al [19] found positive effects of BC in immobilizing Cr in soil and lowering plant accessibility. Moreover, lower plant availability of Cr VI as affected by applied JPBCs could be due to the presence of more active and binding sites on JPBCs' surface, which strengthens its ability in fixing heavy metals [24,25].…”
Section: Effect Of Charred Materials On Root and Shoot Lengths (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower Cr VI availability and plant accessibility showed excellent sorption ability of JBCs and JPBCs [22]. In a review study about ameliorating effects of BC on physio-chemical properties of weather soil, Glaser et al [19] found positive effects of BC in immobilizing Cr in soil and lowering plant accessibility. Moreover, lower plant availability of Cr VI as affected by applied JPBCs could be due to the presence of more active and binding sites on JPBCs' surface, which strengthens its ability in fixing heavy metals [24,25].…”
Section: Effect Of Charred Materials On Root and Shoot Lengths (Cm)mentioning
confidence: 99%
“…Generally, BC produced at high temperature (600-700 • C) has higher aromaticity and recalcitrant potential, but due to dehydration and deoxygenation, has a smaller number of O-and H-containing functional groups [17,18]. Meanwhile, BC produced at low temperature (300-400 • C) has more O-and H-containing functional groups and variety of organic characteristics [19,20]. Herath et al [21] reported a 93-97% decrease in Cr, Ni, and Mn bioaccumulation in tomato plants by the application of BC.…”
Section: Introductionmentioning
confidence: 99%